PERTUMBUHAN DAN PRODUKSI BUNCIS (Phaseolus vulgaris L.) DENGAN PEMBERIAN PUPUK TANDAN KOSONG KELAPA SAWIT DAN NPK - Muhammad Yogi Saputra; Hangger Gahara Mawandha; Tantri Swandari (Program Studi Agroteknologi INSTIPER, 2018)
The research aims to determine the effect of oil palm empty fruit bunches fertilizer and NPK and their interactions on growth and yield of beans (Phaseolus vulgaris L). The study was conducted in the garden of Education and Research Institute for Agriculture KP-2 STIPER Yogyakarta, located in the village Maguwoharjo, Depok, Sleman, Yogyakarta, Sleman regency is located at LU 734.520 - 747.050 and 1070 LS 15'03